Ethical Dilemmas as Seen Through the Major Characters Reflected in "The Danish Girl" Movie Screenplay Written by Lucinda Coxon - Anggraeni, Kemala Putri; Ari Widayanti, Maria Johana (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2019)
An ethical dilemma is an interesting topic to discuss since it always occurs to us in our daily lives whether we realise it or not. The study is aimed to explain the ethical dilemmas of the major characters in The Danish Girl movie screenplay by Lucinda Coxon. This study used psychoanalytic theory of the tripartite model theory by Sigmund Freud and employed qualitative method. The result was the ethical dilemmas of the major characters occurred before they made a decision in their actions. This study revealed that the ethical dilemma happened to them because they needed to think about the impact of their actions on other people or themselves. It could prevent them from doing or saying inappropriate things which could hurt someone's feelings or harm themselves. Another result in this study was that the ethical dilemmas that happened to the major characters mostly represent ego more than the other two parts of psyche. They could control what they wanted to say or do since they thought about the possible things that could happen to each choice before they made the decision. Keywords: Characters, Ethical Dilemma, Movie Screenplay, Psychoanalytic Theory, The Danish Girl